2002
DOI: 10.1016/s0014-5793(02)03259-3
|View full text |Cite
|
Sign up to set email alerts
|

Cis and trans acting factors in the regulation of parathyroid hormone (PTH) mRNA stability by calcium and phosphate

Abstract: Calcium and phosphate regulate parathyroid hormone (PTH) mRNA stability through di¡erences in binding of parathyroid proteins to an element in its 3P P-untranslated region. One of the proteins is AUF1 (A+U-rich element binding factor 1). An in vitro degradation assay showed that transcripts for PTH and chimeric growth hormone (GH)^PTH 63 nt, but not for native GH, were stabilized by PT proteins from rats on low calcium diets and destabilized by proteins from rats on low phosphate diets, correlating with PTH mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 25 publications
1
21
0
2
Order By: Relevance
“…The alternate explanation, that Ca regulates PTH mRNA stability, was supported by their in vitro degradation assays. Subsequent studies identified a cis element in the 3 0 -UTR of rat PTH that targeted reporter transcripts for degradation and that bound cytosolic proteins in a Ca-dependent manner (Moallem et al 1998, Sela-Brown et al 1999, 2000, Kilav et al 2001, Naveh-Many et al 2002; human and bovine 3 0 -UTR were found to have alternative cis-acting protein-binding elements involved in the stabilization of PTH mRNA (Bell Destabilization of PTH mRNA . C S RITTER and others 17 et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…The alternate explanation, that Ca regulates PTH mRNA stability, was supported by their in vitro degradation assays. Subsequent studies identified a cis element in the 3 0 -UTR of rat PTH that targeted reporter transcripts for degradation and that bound cytosolic proteins in a Ca-dependent manner (Moallem et al 1998, Sela-Brown et al 1999, 2000, Kilav et al 2001, Naveh-Many et al 2002; human and bovine 3 0 -UTR were found to have alternative cis-acting protein-binding elements involved in the stabilization of PTH mRNA (Bell Destabilization of PTH mRNA . C S RITTER and others 17 et al 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…The 63-nt element consists of a core 26-nt minimal binding sequence and adjacent flanking regions. The Pth RNA ARE does not contain AUUUA sequences and falls into the class III category of AREs (42,43). Two proteins, AU-rich binding factor 1 (AUF1) and K-homology splicing regulator protein (KSRP), bind the ARE in the 3′ UTR of Pth mRNA (43,44).…”
Section: Figurementioning
confidence: 99%
“…The Pth RNA ARE does not contain AUUUA sequences and falls into the class III category of AREs (42,43). Two proteins, AU-rich binding factor 1 (AUF1) and K-homology splicing regulator protein (KSRP), bind the ARE in the 3′ UTR of Pth mRNA (43,44). AUF1 increases Pth mRNA half-life, whereas KSRP has the opposite effect (43,44).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations